Investigation of the Heat Treatment Regimes on the Structure and Microhardness of Laser Direct Energy Deposition Aluminum Alloy AlSi10Mg - Darya Volosevich; Zhanna Shabunina; Nikita Yurchenko; Ruslan Mendagaliev; Edem Slatenko; Georgii Klimov; Olga Klimova-Korsmik; Aleksey Eremeev (Metals)
This study investigates the influence of various heat treatment regimes on the structure and microhardness of the aluminum alloy AlSi10Mg processed by the L-DED method. The study considers heat treatment regimes for solid solution in the temperature range of 500−540 °C with holding times of 30–120 min, as well as artificial aging regimes in the temperature range of 160−190 °C with holding times of 4–8 h. As a result of studying the structure and mechanical properties of the heat-treated samples, it became clear that the optimal regime can be considered the regime of 500 °C for 30 min followed by 190 °C for 6 h. This regime leads to the formation of a uniform structure with the breakage of the eutectic network into separate spherical silicon inclusions. The microhardness in this case is 90 HV, which is 55% higher than the initial state. Using TEM, it was established that the reason for the increase in hardness is the formation of nanoscale inclusions β″ (Mg5Si6).